First Pacific Rim Manufacturing Company a quality control study - Camacho, Rowena Grace D.; Lachica, Edlyn S.; Moncada, Marchae Gizette B. (Diliman, Quezon City College of Engineering, 2001)
CFirst Pacific Rim Manufacturing Corporation is a company engaged in the production of furniture products for the local and international market. It products range from chairs, beds, tables, stools, and the like. Its major clients range from international hotels, resorts, banks, offices, etc. In studying the company, focus was set on the Claire woven-leather chair design since this chair is the largest-selling product in the company?s line. The study analyzed the product based on the various processes involved in its production. The quality system in place was examined in order to spot various problems that were occurring. Upon gathering all this data, analysis techniques were then applied, namely, the Streamline Analysis, the Ishikawa Diagram, Statistical process Control, Process Capability Analysis, and Acceptance Sampling. A lack of proper inspection, inaccurate in-process of wooden legs, inaccurate in-process inspection of metal frames, and wear and tear of equipment were the four main problems that hampered the company?s over-all quality position. Inaccurate dimensions of finished products, lack of uniformity in wooden legs, lack of uniformity in metal frames was then recognized as the main effects of the main problems. The study applied acceptance sampling to resolve the company?s inefficient quality control system, specifically its purchase of raw materials. The study recommends that the company employ an acceptance sampling based on the military standard 105E. The sampling scheme called for, is as follows: given lots sizes equal to 200 boards, (1) normal inspection: n=50, c=1; (2) tightened inspection: n=50, c=0; (3) reduced inspection: n=20, c=1. This plan will reduce the recurrence in the presence of bad quality wood. In striving to attain a robust control system, that is a system that is dynamic and not susceptible to external factors, it is recommended that regular control charting must be adopted, particularly in the processing of wooden legs and metal frames. For the in-process inspection of wooden legs and metal frames, control charting was applied in order to verify these problems. Process capability was also applied to assess the company?s production process. The results showed that for both wooden legs and metal frames, the processes were capable in producing within specifications; however, the processes were off-centered. For wooden legs, it was recommended that they use a homogenous block for a set of four legs. Accurate values for measurements of the wooden leg and components of the metal frame should be set. Clearer proto-boards should be utilized. Furthermore, the use of precise measuring device is recommended.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: First Pacific Rim Manufacturing Company; Furniture industry and trade; Quality control